Health and Self-Care Literacy - Galvão, Ana Maria (2022)
Nowadays, we often hear the term Health Literacy (HL). We are of the opinion that this term is used interchangeably, sometimes referring to knowledge, information, sometimes referring to attitudes, sometimes referring to training. Therefore, this theme has attracted our attention over the last decade and, as a result of this reflection, resulted in the work Literacy in Health and Self-Care: evidence that project clinical practice (Galvão et al., 2021). The concept of HL is multidimensional, we find a range of definitions which add specific aspects of HL. In this opinion scientific article, we selected definitions and concepts about HL and self-care, we identified the dimensions of HL and assessment methods. We also identify documents available in Portugal that aim to promote it. Based on the evidence, we found that the promotion of HL in the Portuguese population is effectively a priority throughout the various stages of life's trajectory, both in terms of health promotion and self-care in any age group, and consequently in terms of disease prevention. : obesity; cerebrovascular diseases; type II diabetes; mental disorders; dementias; cancer diseases; etc. HL training is based on behavioral changes, so the strategies will have to be focused on tools that enhance human functioning, achieved through the improvement of cognitive, emotional and/or behavioral self-regulation. The European agenda for health highlights HL as a priority, considering the need for the joint involvement of citizens, communities, organizations and health policies.